2021
DOI: 10.1002/cne.25101
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of cone photoreceptor morphology in bowhead and beluga whales

Abstract: The cetacean visual system is a product of selection pressures favoring underwater vision, yet relatively little is known about it across taxa. Previous studies report several mutations in the opsin genetic sequence in cetaceans, suggesting the evolutionary complete or partial loss of retinal cone photoreceptor function in mysticete and odontocete lineages, respectively. Despite this, limited anatomical evidence suggests cone structures are partially maintained but with absent outer and inner segments in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Previous studies demonstrated rod monochromacy in some cetaceans and several mutations in the opsin gene sequence have been reported in cetaceans, suggesting the evolutionary complete or partial loss of cone cell function in the retina, while non-photosensitive cones are maintained (Schweikert et al, 2016). Refined histological and advanced microscopy techniques revealed two cone morphologies in cetacean retinas that are not traditional morphologic cone structures, a consequence of genetic modifications influenced by environmental selection pressure (Smith et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies demonstrated rod monochromacy in some cetaceans and several mutations in the opsin gene sequence have been reported in cetaceans, suggesting the evolutionary complete or partial loss of cone cell function in the retina, while non-photosensitive cones are maintained (Schweikert et al, 2016). Refined histological and advanced microscopy techniques revealed two cone morphologies in cetacean retinas that are not traditional morphologic cone structures, a consequence of genetic modifications influenced by environmental selection pressure (Smith et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…Rod photoreceptors are more sensitive detectors of light than cones and they are capable of detecting single photons (Field and Rieke, 2002). Thus, rod-based vision provides better underwater vision in conditions where light intensity is low and light is scattered with increasing depth (Smith et al, 2021). In deep-diving species, rod dominance and rapid dark adaptation in particular are traits that indicate these marine mammals use vision primarily in low light levels, where colour vision may be of secondary importance (Peichl et al, 2001).…”
Section: Discussionmentioning
confidence: 99%